A giant dumbbell-shaped primitive neuroectodermal tumor in the brain. (6th December 2016) - Lan, Zhi Gang; Chen, Mao Jun; Li, Jin; Liu, Yanhui
Abstract : A 5-year-old girl presented with an 8 × 10-cm dumbbell-shaped mass in her left occipitoparietal region (figure 1). A preoperative CT angiogram demonstrated a large subcutaneous mass with abundant blood vessels (figure 2A). MRI revealed a giant extracranial–intracranial space-occupying lesion (figure 2, B–D). After endovascular embolization, we resected the tumor (figure 2E). The postoperative pathologic diagnosis was primitive neuroectodermal tumor (figure 2F). Primitive neuroectodermal tumor extension to the brain is rare; imaging is not pathognomonic and requires confirmation by pathology. Early intervention is preferable.